Impacts of the COVID-19 pandemic on the routine of university students: an integrative review on mental health (Research, Society and Development, 2022)
The global impact of the pandemic on the health system, politics, economy and education, as well as the oral and written news explore this theme, constantly showing the number of people who contract and die from COVID-19 every day, which can cause psychological changes. Therefore, this research aims to analyze the available productions, highlighting those with the greatest contribution on the impacts of the COVID-19 pandemic on the daily life and mental health of university students. This is an integrative review, a method that allows criticizing and synthesizing the knowledge produced in an orderly and systematic way, with the purpose of generating a consistent and meaningful whole through findings from diverse and representative studies on a given topic. As a result, it was possible to identify the main factors and repercussions that affected the daily life and mental health of students in the university context amid the COVID-19 pandemic, in addition to bringing reflections that can contribute to improving the monitoring of the mental health of this academic community. through interventions that prioritize their well-being.